Implementasi Problem-Based Learning Dalam Meningkatkan Self-Regulated Learning Mahasiswa Pada Mata Kuliah Akuntansi Lanjutan - Mutiya Oktariani; Ahmad Supendi (Politeknik Negeri FakFak, 2024)
This study aims to reveal (i) the improvement of self-regulated learning skills (SRL) through problem-based learning (PBL), and (ii) the improvement of lecturers’ performance in implementing PBL. To achieve these purposes, a lesson study with two cycles was conducted. Each cycle consisted of plan phase, do phase, and see phase. The study was conducted to the 3rd semester Advance Accounting Students at Musamus University who attended the Introduction to Accounting course. There were 40 students as the research subjects. The sampling technique used to collect data regarding SRL was questionnaires which were flled out by the students; while the data regarding the lecturer’s performance was collected by observation sheets that were flled out by students and members of lesson study group. The study has proved that: (i) the implementation of PBL could improve SRL even though the level of achievement was still not optimal, and (ii) the level of achievement of the lecturer’s performance in implementing PBL was optimal and improving